PENERAPAN PENDIDIKAN DASAR MILITER (DIKSARMIL) DALAM MEMBENTUK KEPRIBADIAN RESIMEN MAHASISWA INSTITUT AGAMA ISLAM NEGERI (IAIN) PALU - Oyan D. Taufiq K.; Hairuddin Cikka; Suharto, Suharto (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
The application of basic education in shaping the mentality and personality of the student regiment at IAIN Palu so that it can shape the mental and personality of the menwa members at IAIN Palu. The inhibiting factors in the process of applying basic education in boosting the mental and personality of the menwa in IAIN Palu are the equipment for training activities, the quantity of menwa in IAIN Palu, and the members of the menwa having difficulty spending time. Supporting factors are the support of the institute, the Central Sulawesi Menwa Commander, and the support of the Menwa alumni. The implementation of basic education in shaping mental and personality is the manifestation of the character of Cinta Tanah Air in the Student Regiment of the State Islamic Institute of Palu (IAIN) Palu which is carried out through education, coaching, and activities, in the implementation of basic education in shaping mental and personality in the Student Regiment of the Institute of Religion Islamic State (IAIN) Palu for Guides and Senior Student Regiments should be more active, and need to be regulated in a specific regulation, to be more clear and detailed.